1994
DOI: 10.1038/ng0994-22
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the p16 gene (CDKN2) as a candidate for the chromosome 9p melanoma susceptibility locus

Abstract: A locus for familial melanoma, MLM, has been mapped within the same interval on chromosome 9p21 as the gene for a putative cell cycle regulator, p16INK4 (CDKN2) MTS1. This gene is homozygously deleted from many tumour cell lines including melanomas, suggesting that CDKN2 is a good candidate for MLM. We have analysed CDKN2 coding sequences in pedigrees segregating 9p melanoma susceptibility and 38 other melanoma-prone families. In only two families were potential predisposing mutations identified. No evidence w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
441
1
8

Year Published

1996
1996
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 777 publications
(462 citation statements)
references
References 20 publications
6
441
1
8
Order By: Relevance
“…The only sequence variation identified in nine DNA samples was G to A transition at position 442 leading to a missense mutation at codon 148 (Ala148Thr). The Ala148Thr missense mutation is considered as a polymorphism based on several observations: it has been previously reported in individuals from the general, average risk, population in ethnically diverse groups: 8% of the Jewish population (Yakobson et al, 2000), 4% of the population in Utah (Kamb et al, 1994) and 5% in the UK population (Bertram et al, 2002). Furthermore, this missense mutation did not segregate with the phenotype in familial melanoma (Hussussian et al, 1994;Harland et al, 1997), and is situated outside the critical four ankyrin repeat domains of p16, and thus does not appear to have any effect in vitro on binding to CDK4 (Ranade et al, 1995;Lilischkis et al, 1996;Harland et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The only sequence variation identified in nine DNA samples was G to A transition at position 442 leading to a missense mutation at codon 148 (Ala148Thr). The Ala148Thr missense mutation is considered as a polymorphism based on several observations: it has been previously reported in individuals from the general, average risk, population in ethnically diverse groups: 8% of the Jewish population (Yakobson et al, 2000), 4% of the population in Utah (Kamb et al, 1994) and 5% in the UK population (Bertram et al, 2002). Furthermore, this missense mutation did not segregate with the phenotype in familial melanoma (Hussussian et al, 1994;Harland et al, 1997), and is situated outside the critical four ankyrin repeat domains of p16, and thus does not appear to have any effect in vitro on binding to CDK4 (Ranade et al, 1995;Lilischkis et al, 1996;Harland et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of genetic changes found in primary lung tumors are characteristic of, but not speci®c for, either NSCLC or SCLC. NSCLC specimens contain activating K-ras mutations in 20 ± 50% of the tumors (Rodenhuis and Slebos et al, 1990;Mills et al, 1995); 50% have deletions or mutations of p53 (Kondo et al, 1992;Mitsudomi et al, 1992); 60% show deletion or reduced expression of p16 INK4a (Kamb et al, 1994;Okamoto et al, 1994Okamoto et al, , 1995Merlo et al, 1995;Shapiro et al, 1995;Xiao et al, 1995); and up to 30% show deletion or reduced expression of Rb (Xu et al, 1991;Reissmann et al, 1993). SCLC specimens demonstrate overexpression of the myc family of protooncogenes due to gene ampli®cation in 10 ± 40% of the tumors (Little et al, 1983;Johnson et al, 1987;Takahashi et al, 1989;Noguchi et al, 1990); 80% have p53 mutations or deletions Hensel et al, 1991;Takahashi et al, 1991;Sameshima et al, 1992); and 90% have deletions of Rb (Yokota et al, 1988;Hensel et al, 1990).…”
Section: Human Lung Cancer: Molecular Characterizationmentioning
confidence: 99%
“…When pRb is phosphorylated in these complexes the E2F proteins are free to transactivate their target genes and their products promote cell cycle progression (Sherr, 1996). Mutation of INK4a was ®rst demonstrated in familiar melanoma (Hussussian et al, 1994;Kamb et al, 1994) and INK4a remains the only member of the INK4 family shown to act as a tumor suppressor gene in humans. Mutation, deletion, or methylation of INK4a is common in many tumors, with a frequency ranging from approximately 30% in esophageal tumors, to nearly 100% in pancreatic carcinomas (Caldas et al, 1994;Ruas and Peters, 1998;Schutte et al, 1997).…”
Section: Introductionmentioning
confidence: 99%